Enhancing Tropical Artificial Forests With Cubic Picture Fuzzy Fairly Aggregation Operators - Ashraf Al-Quran; Rukhsana Kausar; Toqeer Jameel; Muhammad Riaz (IEEE Access, 2023)
The creation of sustainable artificial tropical forests is of utmost importance for addressing critical environmental issues like deforestation, habitat loss, and climate change. This research paper presents an innovative approach that considers ecological, socioeconomic, and technological factors. The proposed approach integrates multi-criteria decision-making (MCDM) methods that take into account the preferences and opinions of stakeholders. To analyze the various criteria involved, cubic picture fuzzy numbers (CPFNs) are utilized. To ensure fairness in evaluating CPFNs, the study focuses on developing operational laws and aggregation operators that promote neutrality and fairness. Specifically, the paper introduces the “cubic picture fuzzy fairly weighted average (CPFFWA) operator” and the “cubic picture fuzzy fairly ordered weighted averaging (CPFFOWA) operator.” By considering stakeholders and prioritizing their long-term sustainability and resilience, this approach proves to be highly valuable for policymakers, forest managers, and other relevant parties. This research avenue bridges the gap in current literature where limited exploration of fairly aggregation operators in tandem with picture fuzzy sets within tropical forest contexts exists. Ultimately, the research strives to contribute to the practical management of these vital ecosystems, fostering environmental conservation and sustainability through a cross-disciplinary approach amalgamating ecology, fuzzy logic, decision theory, and environmental science.